Blockade of Toll-Like Receptors (TLR2, TLR4) Attenuates Pain and Potentiates Buprenorphine Analgesia in a Rat Neuropathic Pain Model. (29th December 2015) - Jurga, Agnieszka M.; Rojewska, Ewelina; Piotrowska, Anna; Makuch, Wioletta; Pilat, Dominika; Przewlocka, Barbara; Mika, Joanna
Abstract : Accumulating evidence indicates that microglial TLR2 and TLR4 play a significant role in nociception. Experiments were conducted to evaluate the contribution of TLR2 and TLR4 and their adaptor molecules to neuropathy and their ability to amplify opioid effectiveness. Behavioral tests (von Frey's and cold plate) and biochemical (Western blot and qRT-PCR) analysis of spinal cord and DRG tissue were conducted after chronic constriction injury (CCI) to the sciatic nerve. Repeated intrathecal administration of LPS-RS (TLR2 and TLR4 antagonist) and LPS-RS Ultrapure (TLR4 antagonist) attenuated allodynia and hyperalgesia. Biochemical analysis revealed time-dependent upregulation of mRNA and/or protein levels of TLR2 and TLR4 and MyD88 and TRIF adaptor molecules, which was paralleled by an increase in IBA-1/CD40-positive cells under neuropathy. LPS-RS and LPS-RS Ultrapure similarly influenced opioid analgesia by enhancing the effectiveness of buprenorphine but not morphine. Summing up, in light of their upregulation over the course of pain, both TLR2 and TLR4 may indeed play a significant role in neuropathy, which could be linked to the observed activation of IBA-1/CD40-positive cells. Blockade of TLR2 and TLR4 produced analgesia and enhanced buprenorphine's effectiveness, which suggests that they may be a putative target for future pharmacological pain relief tools, especially for opioid rotation, when the effect of morphine is tolerated.